A (re)significação conceptual nas práticas colaborativas com professores do Ensino Fundamental - Andrade Júnior, Francisco Vitorino de (2005)
The work objectified to apprehend the degree of the teachers' concept concerning the territory concept and to intervene with situations of critical reflections to accompany and to analyze the process of conceptual elaboration. It contemplates on the (new)meaning of knowledge and (new)elaboration of the concept in study done inside a pedagogic intervention. The Municipal School Dr. Julio Senna - Ceará-Mirim/RN and six (6) teacher-collaborators that taught in the 3rd and 4th grades of the fundamental teaching, constitutes the empiric field of the research. Its theoretical-methodological contributions are built in the studies of Vigotski (2000a, 2000b and 2001) on the formation process and development of concepts; in the methodology colaborate (Ibiapina (2004), Bartomé (1986), Kemmis and Mctaggart (1988), Arnal, Del Ricon and Latorre (1992), Pepper and Ghedin (2002), among others) and in the critical-reflexive conception of the Geography (Soares Júnior (2000 and 1994), Silva (1998), Raffestin (1993), Santos (1994), Felipe (1998), among others). The accomplishment of the work presupposed starting from the reflections on the following subjects: which the teachers' understanding in the school space concerning the territory concept? How does happen the process of conceptual construction territory for the teachers? The analysis of the teachers' previous knowledge on the concept in study, evidenced that its apprehensions on the attributes of the referred concept went mentioned the to light of the perceptible dimension of the real-concrete relationships of the reality linked to the degree of the spontaneous concepts and followed by the ideas of the traditional, humanistic and cultural geographical conceptions (positivism and phenomenology), restricting the territory meaning the notion of State-Nation and place of the men's dwelling. In the intervention process, it was verified to real possibility of the acquisition of indispensable scientific concepts to the process of (new)meaning conceptual of geographical knowledge through the continuous practice of the educational formation, when it was evidenced that the teacher-collaborators acquired high degrees of attributions of the significance of the territory concept to the they elaborate generalizations by means of analyses and syntheses of the concept-attribute (essential and multiples) of the reference conceptual in study